Design of learning applications using the Rapid Application Development method. Issue 2 (March 2021) - Maulany, R; Hasan, B; Abdullah, A G; Rohendi, D
Abstract: Information and Communication Technology (ICT) in the current era of globalization has become a fundamental requirement in supporting the effectiveness and quality of the education process. Educational issues in Indonesia such as the quality and relevance of education, access and equity in education, geographical range, education management, autonomy and accountability, efficiency and productivity, budget and sustainability, cannot be overcome without the help of ICTs. ICT-based education is a means of interaction between management and administration of education, which can be used by both educators and education staff and students in improving the quality, productivity, effectiveness and access to education. The purpose of this study is to find out how to design e-learning applications in informal and non-formal education, as well as efforts to improve the use of e-learning in informal and non-formal education. So that the results of this study can be improved the quality of informal and non-formal education, and can facilitate the field of education in Indonesia by using information technology as an interactive learning medium. The method developed in designing e-learning applications is to use a method that is generally used in the development of information systems using Rapid Application Development. The system that has been built can provide information about distance learning in informal and normal education. In addition, the system that has been built can accelerate the learning process for students / tutors. Therefore, it does not take long in the learning process and to get new material from the teacher. Moreover, the system built can facilitate users in learning and communicating with teachers when there is information needed / needed from the teacher.